AB0595 THE USEFULNESS OF 18F-FLUORODEOXYGLUCOSE POSITRON EMISSION TOMOGRAPHY CT (18F-FDG PET/CT) AS AN IMAGING BIOMARKER IN TAKAYASU ARTERITIS TREATED WITH TOCILIZUMAB. (June 2019) - Kato, Mikiya; Okuda, Hanae; Kameda, Tomohiro; Miyagi, Taichi; Wakiya, Risa; Nakashima, Shusaku; Shimada, Hiromi; Fahmy Mansour, Mai Mahmoud; Yamamoto, Yuka; Dobashi, Hiroaki
Abstract : Background: Disease activity in large vessel vasculitis (LVV) including TAK is traditionally assessed by clinical and serological (ESR, CRP) parameters. Imaging assessment, including FDG-PET, may also be useful to monitor LVV. On the other hand, Tocilizumab (TCZ) treatment showed a favorable trend toward refractory Takayasu arteritis (TAK) (1). Because the TCZ could suppress the CRP or ESR elevation strongly despite the exist of TAK disease activity, clinical and serological (ESR, CRP) parameters could not reflect the disease activity of TAK appropriately. Objectives: This study objective was to determine the efficacy of 18F-FDG PET/CT on the evaluating the disease activity of TAK treated TCZ compared with clinical and serological parameters. Methods: Five Patients with TAK were recruited into a prospective, observational cohort. All patients in this study underwent FDG-PET/CT scans at 6 - 12 month intervals before and after TCZ treatment. Serological (ESR, CRP) and clinical assessment were determined at each visit. Disease activity was determined whether scans were active or inactive based on visual inspection of arterial 18F-FDG uptake. To determine the score of arterial FDG uptake assessed qualitatively relative to liver activity in 10 vascular beds with higher scores indicating more vascular inflammation. Additionally, scoring of FDG uptake was conducted to caluculate as divided into 4 grade compared with liver activity: 0, no uptake present; I, low-grade uptake (uptake present but lower than liver uptake); II, intermediate-grade uptake (similar to liver uptake); III, high-grade uptake (higher than liver uptake) (2). Clinical and imaging assessments were performed blinded to each other. Results: All 5 cases (one male and 4 female) were initiated by TCZ treatment. The average age was 42.2±11.6 years old. The disease duration at the administration of TCZ was 176±136 months. The mean dosage of PSL was 6.40±3.72 mg/day. After initiating TCZ treatment, mean CRP values decreased from 1.44±1.80 to 0.032±0.034, and the PSL dose was reduced to 4.00±2.61 mg/day. No serious adverse events were observed. Though serum level of inflammatory biomarker such as CRP or ESR had become into normal range in all patients, arterial 18F-FDG uptake also remained in all patients after TCZ treatement. Additionally, clinical manifestations were correlate with site numbers and score of FDG uptake. The change of FDG score could reflect the improvement of clinical manifestation compared than serological biomarkers. Conclusion: Serological biomarker such as CRP or ESR could not reflect disease activity appropriately in TAK patients treated with TCZ. 18F-FDG PET/CT was more useful for evaluating disease activities in Takayasu arteritis treated with TCZ. Further study might be needed to determine the definition of complete remission in TAK patients treated with TCZ. References: [1] Nakaoka Y, Isobe M, Takei S, et al. Ann Rheum Dis 2018;77:348–354 [2] Ingo Einspieler, et al. Eur J Nucl Med Mol Imaging 2015 42:1012–1024 [3] Quinn KA, et al. Ann Rheum Dis 2018;77:1166–1172. Disclosure of Interests: None declared